Factores biopsicosociales relacionados a la conducta suicida en adolescentes del albergue Santa Mónica Iquitos 2024 - Grandez del Aguila, Jassery Anahy (2025)
The present research aimed to determine the biopsychosocial factors (age, sex, self-esteem, anxiety, depression, alcohol and drug use) related to suicidal behavior in adolescents aged 10 to 19 years at the Santa Monica shelter in Iquitos 2024. The study was quantitative, with a non-experimental, descriptive, cross-sectional design, and included a sample of 102 adolescents aged 10 to 19 years of both sexes. The survey technique was used, and the following instruments were used: Biosocial Factors Questionnaire, Rosenberg Self-Esteem Scale, Zung Anxiety Rating Scale, Zung Depression Self-Rating Scale, and Beck Suicidal Ideation Scale. The x2 statistical test was used for hypothesis testing, with a significance level of α = 0.05. The results show a significant relationship between the psychological factors: self-esteem (p = 0.011 < 0.05), anxiety (p = 0.001 < 0.05), depression (p = 0.001 < 0.05) and suicidal behavior. There is no significant relationship between the biological factors: age (p = 0.329 > 0.05), sex (p = 0.940 > 0.05) and suicidal behavior and social factors, alcohol use (p = 0.937 > 0.05), drug use (p = 0.535 > 0.05) and suicidal behavior. Therefore, it is concluded that there is a statistically significant relationship between psychological factors and suicidal behavior in adolescents at the Santa Monica shelter in Iquitos 2024.